Interactions between European Court of Human Rights and Private International Law of European Union - Liakopoulos, Dimitris (CUADERNOS DE DERECHO TRANSNACIONAL, 2018)
The present work is concentrated on the analysis of the jurisprudence between the European Court of Human Rights and the European Court of Justice in the sector of private international law. In particular, it deals with the differences, similarities, influences, impact, etc. in the sector of family law, insolvency and succession according the Regulations and the private international law and last but not least the recognition of sentences by the European Member States.